Republic of Yemen : Health Sector Strategy Note - World Bank (Washington, DC, 2013)
This report is intended to provide a base for discussions of Yemen's health sector strategy with the Government of Yemen (GOY) and other donors in light of the Ministry of Public Health (MOPH) initiative of Health Sector Reform (HSR) as well as the potential areas of World Bank support. The report is divided in nine sections. Section A provides the introduction to the report and the country context. Sections B and C review the key health indicators and trends and the key aspects of the sector in terms of financing, service delivery, human resources, health services, organizational framework, and policy environment. Sections D and E provide international comparisons and an assessment of the sector performance with regard to health outcomes, equity, access, efficiency, quality, and sustainability. Section F is an outline of the MOPH/HSR program. Sections G and H provide an overview of the Bank's current assistance and its response to HSR as well as the different donors' support. Finally, Section I outlines the future areas where the Bank can support the government in its health reform efforts. Yemen faces major challenges to improving the health status of its population, which go beyond the health delivery network. Poverty, low participation in education especially among girls, and high illiteracy are major contributing factors to poor health as are limited access to potable water and proper sanitation.